ACTIVE OR PASSIVE? “I” OR “WE?” - Lyudmila B. Kuznetsova; Svetlana A. Suchkova (Высшее образование в России)
The article invites researchers and teachers of Academic English to reflect on the conventions they use and teach concerning academic genres, especially research publications. We consider some of the existing trends in using active and passive verb forms and personal pronouns in journal publications.